The Case for XQuery XML adoption is growing steady. - King, Jerry
XML use is widespread across modern information systems in all industry, government and academic sectors. The core technologies for processing XML (XML, XSLT, XPath, XML Schema, and others) are maturing steadily-thanks to support from standards bodies like the W3C and OASIS, and from major industry players such as IBM, Microsoft and Oracle. XML is also the basis for a growing body of industry standards for data exchange, and it is well on its way to becoming a mainstream technology for data integration. XML is transforming not just data-it is transforming information processing in general.